Translocation of p21Cip1/WAF1 from the nucleus to the cytoplasm correlates with pancreatic myofibroblast to fibroblast cell conversion. Issue 6 (11th May 2005) - Manapov, F; Muller, P; Rychly, J
Abstract : Background and aims: In the pancreas, myofibroblasts (MFBs) were shown to play an important role in the cellular response during inflammation and injury. However, there is only fragmentary information concerning the fate of these cells in pancreas regeneration and fibrosis development. Methods: Explant cultures of rat pancreatic tissue were used as a model to follow cellular dynamics and phenotype conversion of pancreatic MFBs in vitro. For detailed biochemical analyses a pancreatic fibroblast cell line (long culture fibroblast (LCF)) was generated from MFBs in a long term culture. Cerulein induced acute pancreatitis and dibutyltin dichloride induced pancreas fibrosis were used as experimental models for acute and chronic fibrogenic reactions, respectively. Results: In the explant culture, pancreatic MFBs which derived from fat storing fibroblastic cells underwent apoptosis or converted again to fibroblasts. The phenotype switch to fibroblasts was associated with translocation of p21 Cip1/WAF1 from the nucleus into the cytoplasm. Molecular analyses in LCFs revealed subsequent binding to and inhibition of the activities of Rho kinase 2 and apoptosis signal regulating kinase 1. In the experimentally established pancreas fibrosis, fibroblasts with cytoplasmic expression of p21 Cip1/WAF1 were distributed throughout fibrotic bands whereas in experimental acute pancreatitis MFBs with nuclear expression of p21 Cip1/WAF1 dominated. Conclusions: The results indicate that pancreatic MFBs are transient and suggest that intracellular localisation of p21 Cip1/WAF1 can contribute to the phenotype conversion of these cells to fibroblasts in culture and experimental injury.